INTEGRATION AND/OR REINTEGRATION OF THE INTERNALLY DISPLACED PERSONS FROM THE ARMED CONFLICT IN THE REPUBLIC OF MACEDONIA OF 2001 (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2015)
After the conflict of 2001 in the Republic of Macedonia, of the initial 76 000 internally displaced persons (IDPs) only 600 remained displaced. Today they are located in collective centers, as well as in private apartments. An equally important, even a key issue is if those who returned are still in their homes. The term ‘reintegration process’ usually means creating conditions for normal living and gradual inclusion of the persons who returned in all spheres of life in their place of origin. Remaining longer in the “foreign” territory inevitably brings changes in identity and identification of the IDP, changes in perception of the IDP towards the new environment, but also a change of the individual, collective and public discourses on IDPs in general.